Flavopiridol inhibits TGF-β-stimulated biglycan synthesis by blocking linker region phosphorylation and nuclear translocation of Smad2 - Rostam, Muhamad Ashraf; Shajimoon, Aravindra; Kamato, Danielle; Mitra, Partha; Piva, Terence J.; Cao, Yingnan; Zheng, Wenhua; Osman, Narin; Little, Peter J. (American Society for Pharmacology and Experimental Therapeutics, 2018)
Transforming Growth Factor (TGF) β is a pleiotropic growth factor implicated in the development of atherosclerosis for its role in mediating glycosaminoglycan (GAG) chain hyperelongation on the proteoglycan biglycan, a phenomenon that leads to increased binding of atherogenic lipoproteins in the wall of blood vessels. TGF-β signalling pathway components leading to the modification of GAG chains on biglcyan are therefore potential targets for the treatment of atherosclerosis. Phosphorylation of the transcription factor Smad has emerged as a critical step in the signalling pathways that control the synthesis of biglycan, both the core protein and the GAG chains. We have previously shown that flavopiridol, a well known cyclin dependent kinase (CDK) inhibitor inhibited biglycan synthesis. We have used flavopiridol to study the role of linker region phosphorylation in the TGF-β-stimulated synthesis of biglycan. We used radiosulfate incorporation and SDS PAGE to assess proteoglycan synthesis; RT PCR to assess gene expression and chromatin immunoprecipitation (ChIP) to assess the binding of phosphorylated Smads to the promoter region of GAG synthesis genes. Flavopiridol blocked TGF-β-stimulated synthesis of mRNA for the GAG synthesizing enzymes, chondroitin 4-sulfotransferase (C4ST-1), chondroitin sulfate synthase-1 (ChSy-1), and xylosyltransferase-1 (XT-1); as well as biglycan core protein mRNA and protein expression. The incorporation of radiosulfate into proteoglycans stimulated by TGF-β as well as GAG hyperelongation were also blocked by flavopiridol. Flavopiridol blocked TGF-β-stimulated Smad2 phosphorylation at both the serine triplet and the isolated threonine residue in the linker region. The binding of polyphosphorylated Smad to the promoter region of the C4ST-1 and ChSy-1 genes was stimulated by TGF-β and this response was blocked by flavopiridol demonstrating that linker region phosphorylated Smad can pass to the nucleus and positively regulate transcription. These results demonstrate the validity of the kinases, which phosphorylate the Smad linker region as potential target(s) for the development of a therapeutic agent to prevent atherosclerosis.